Simulation of high strain rate properties of magnesium alloy AZ91D - Song, Zi Hao (2014)
Low density and excellent machinability of Mg alloys make them good candidates for light-weight constructions of components in the engineering industry. Furthermore, they also exhibit much better complex mechanical behavior than more common materials.